Costs of dementia with lewy bodies: A Chinese multicenter cross‐sectional study. (3rd December 2022) - Guo, Xia; Meng, Qingbo; Zuo, Meimei; Su, Zhou; Gan, Jinghuan; Li, Xu‐Dong; Zhu, Hongcan; Gang, Baozhi; Niu, Jinping; Liu, Shuai; Ji, Yong
Abstract: Introduction: Dementia with Lewy bodies (DLB) significantly increases the economic burden on caregivers and society, but few studies have focused on the costs. This study aims to evaluate the current economic costs of DLB and its related factors. Methods: A total of 193 patients diagnosed with probable DLB were consecutively enrolled from 6 memory clinics between August 2017 to July 2021. Data were collected from August to December of 2021, patients' per capita annual economic costs related to DLB in the year preceding the interview were evaluated, and factors related to the costs were assessed using regression analysis. Results: Patients with DLB led to per capita annual total costs of US 21, 378.3 in 2021, with direct medical costs, direct non‐medical costs and indirect costs of US 3471.4, US 3946.4 and US 13, 960.5, respectively, accounting for 16.2%, 18.5% and 65.3%, of total costs. Factors related to the costs of DLB showed that impairments in activities of daily living (ADL) and caregivers' subjective burden had a greater impact on the total, direct medical and indirect costs. Conclusion: The economic burden of DLB in China is huge, and indirect costs account for the largest proportion, serious impairment of the ADL and the subjective burden of caregivers, which possibly has a greater effect on costs. The substantial contributions made by family members and other unpaid caregivers of DLB should be fully recognized in strategic policy discussions and in case‐level planning and assessments. Key points: The considerable total societal economic burden of Dementia with Lewy bodies (DLB) includes direct medical costs, non‐direct medical costs and indirect costs (largely informal care costs, but also intangible costs). Indirect costs account for the largest proportion of DLB economic burden. Impairment of ADL and the subjective burden of caregivers has a greater effect on costs.